Lb3.250 A comparative analysis of costs of single and dual rapid hiv and syphilis diagnostics: results from a randomised control trial in colombia. (8th July 2017) - Obure, Carol Dayo; Gaitan, Hernando; Saenz, Ricardo Losada; Gonzalez, Lina; Angel-Muller, Edith; Laverty, Maura; Perez, Freddy
Abstract : Introduction: HIV and congenital syphilis are major public health burdens contributing to substantial perinatal morbidity and mortality globally. Although studies have reported on the costs and cost effectiveness of rapid diagnostic tests (RDTs) for syphilis screening within antenatal care in a number of resource constrained settings, empirical evidence on country specific cost and estimates of single RDTs compared to dual RDTs for HIV and syphilis are limited. Methods: A cluster randomised control study design was used to compare the incremental costs of two testing algorithms: 1) single RDTs for HIV and syphilis; and 2) dual RDTs for HIV and syphilis, in 12 health facilities in Bogotá and Cali, Colombia. The costs of single HIV and syphilis RDTs and dual HIV and syphilis RDTs were collected from each of the health facilities. The economic costs per woman tested for HIV and syphilis and costs per woman treated for syphilis defined as the total costs required to test and treat one woman for syphilis were estimated. Results: A total of 2214 women were tested in the study facilities. Cost per pregnant woman tested and cost per woman treated for syphilis were $10.26 and $607.99 respectively in the single RDT arm. For the dual RDTs, the cost per pregnant woman tested for HIV and syphilis and cost per woman treated for syphilis were $15.89 and $1, 859.26 respectively. Overall costs per woman tested for HIV and syphilis and cost per woman treated for syphilis were lower in Cali compared to Bogotá across both intervention arms. Staff costs accounted for the largest proportion of costs while treatment costs comprised less than 1% of the preventive program. Conclusion: Findings show lower average costs for single RDTs compared to dual RDTs with costs sensitive to personnel costs and the scale of output at the health facilities.